Perceptions of Approved Clinical Instructors: Barriers in the Implementation of Evidence-Based Practice - Hankemeier, Dorice A. (National Athletic Trainers Association, 2013)
CONTEXT: As evidence-based practice (EBP) becomes prevalent in athletic training education, the barriers that Approved Clinical Instructors (ACIs) experience in implementing it with students need to be understood. OBJECTIVE: To investigate barriers ACIs face when implementing EBP concepts in clinical practice and in teaching EBP to professional athletic training students and to investigate the educational emphases to improve the barriers. DESIGN: Qualitative study. SETTING: Telephone interviews. PATIENTS OR OTHER PARTICIPANTS: Sixteen ACIs (11 men, 5 women; experience as an athletic trainer = 10 ± 4.7 years, experience as an ACI = 6.81 ± 3.9 years) were interviewed. DATA COLLECTION AND ANALYSIS: We interviewed each participant by telephone. Interview data were analyzed and coded for common themes and subthemes regarding barriers and educational emphases. Themes were triangulated through multiple-analyst triangulation and interpretive verification. RESULTS: Barriers to EBP incorporation and educational emphasis placed on EBP were the main themes reported. Resources, personnel, and student characteristics were subthemes identified as barriers. Resource barriers included time, equipment, access to current literature, and knowledge. Coworkers, clinicians, and coaches who were unwilling to accept evidence regarding advancements in treatment were identified as personnel barriers. Programmatic improvement and communication improvement were subthemes of the educational emphasis placed on EBP theme. The ACIs reported the need for better integration between the clinical setting and the classroom and expressed the need for EBP to be integrated throughout the athletic training education program. CONCLUSIONS: Integration of the classroom and clinical experience is important in advancing ACIs' use of EBP with their students. Collaborative efforts within the clinical and academic program could help address the barriers ACIs face when implementing EBP. This collaboration could positively affect the ability of ACIs to implement EBP within their clinical practices.